Pengaruh NPL, LDR, Terhadap ROA dengan NIM sebagai Variabel Intervening Pada Bank BUMN yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2023 - Cherly Dwi Meivia; Fitriyadi (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: Return on Asset (ROA) is a ratio that shows the results (return) on the amount of assets used in the company. Bad loans and the amount of credit disbursed have an impact on Return on Asset (ROA). This study aims to determine and test the effect of Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) on Return on Asset (ROA) with Net Interest Margin (NIM) as an Intervening Variable in State-Owned Banks Listed on the Indonesia Stock Exchange (IDX). This research is a quantitative method research with an explanatory research design. The population in this study is all financial reports of state-owned banks listed on the Indonesia Stock Exchange (IDX). The sample size used is the financial reports of state-owned banks listed on the Indonesia Stock Exchange (IDX) for the period 2016-2023 with a sampling technique of purposive sampling. The type of data used in this study is secondary data in the form of financial reports obtained from the Indonesia Stock Exchange (IDX). Data collection techniques by documentation. The data analysis technique in this study uses path analysis with the EViews 12 program. The results of this study prove that Non-Performing Loan (NPL) has a significant effect on Net Interest Margin (NIM). Loan to Deposit Ratio (LDR) does not have a significant effect on Net Interest Margin (NIM). Non-Performing Loan (NPL) has a significant effect on Return on Asset (ROA). Loan to Deposit Ratio (LDR) does not have a significant effect on Return on Asset (ROA). Net Interest Margin (NIM) has a significant effect on Return on Asset (ROA). Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) do not have a significant effect on Return on Asset (ROA) through Net Interest Margin (NIM.)